THE PROBLEMS OF RELATIONSHIP BETWEEN STUDENTS AS A KEY FACTOR OF SELF- DEVELOPMENT IN LEARNING FOREIGN LANGUAGES - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
This articles considers problems of development relationship between students as essential part for their self-development in the process of learning foreign languages. As the author regards, in order to create good conditions for best learning foreign languages, bases for communicative relations between students should be in priority. Thus, the choice of rational forms of organization of the educational process becomes of paramount importance